Compensation and Principal Leadership as Determinants of Teachers’ Teaching Discipline - Vivi Kesumah; Tri Widayatsih; Muhammad Fahmi (Yayasan Sembilan Pemuda Indonesia, 2027)
This study examines the effects of compensation and principal leadership on teachers’ teaching discipline in public elementary schools. A quantitative explanatory survey was conducted among teachers working in public elementary schools in Talang Kelapa District. The population consisted of 173 teachers, and 58 complete questionnaires were included in the final analysis. Data were collected using three 30-item Likert-scale instruments measuring compensation, principal leadership, and teaching discipline. All instruments demonstrated strong validity and very high internal consistency. Descriptive analysis, normality testing, simple linear regression, partial t-tests, multiple regression, and an F-test were performed using statistical software. The results indicate that compensation has a positive and significant effect on teaching discipline, with a regression coefficient of 0.940, a t-value of 51.613, and a significance level below 0.001. Principal leadership also has a positive and significant effect, with a regression coefficient of 0.938, a t-value of 51.281, and a significance level below 0.001. The simultaneous test confirms that compensation and principal leadership jointly influence teaching discipline, producing an F-value of 67,317.737 with significance below 0.001. These findings show that teachers are more likely to demonstrate punctuality, instructional preparedness, compliance with school procedures, and administrative responsibility when they perceive compensation as fair and leadership as clear, supportive, consistent, and exemplary. The study emphasizes that teaching discipline should be managed through an integrated approach combining equitable rewards, professional recognition, effective supervision, communication, and consistent organizational expectations. It offers practical direction for strengthening teacher management in schools.